Are there any benefits of using an inlay graft in the treatment of primary hypospadias in children?: a systematic review and metanalysis - Silay, Mesrur Selcuk; 't Hoen, Lisette; Bhatt, Nikita; Quaedackers, Josine; Bogaert, Guy; Dogan, Hasan Serkan; Nijman, Rien J. M.; Rawashdeh, Yazan; Stein, Raimund; Tekgul, Serdar; Radmayr, Christian (Journal of pediatric urology, 2021)
Introduction - Dorsal inlay graft urethroplasty (DIGU) has been described as an effective method for hypospadias repair with the proposed advantage of reducing the risk of complications. We aimed to systematically assess whether DIGU has any additional advantages over standard tubularized incised plate urethroplasty (TIPU) repair in children with primary hypospadias. - Materials and methods - This systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. The a priori protocol is available at the PROSPERO database (CRD42020168305). A literature search was conducted for relevant publications from 1946 until January 10, 2020 in seven different databases. Randomized controlled trials (RCTs), comparative studies (TIPU vs DIGU) and single arm case series (>20 cases) of DIGU were eligible for inclusion. Secondary hypospadias, two-stage repairs, disorders of sex development, significant curvature of >30°, and a mean or median follow-up of less than 12 months were excluded. - Discussion - A total of 499 articles were screened and 14 studies (3 RCTs, 5 non-randomized studies (NRSs), and 6 case series) with a total of 1753 children (distal: 1334 (76%) and proximal: 419 (24%)) were found eligible. Mean follow-up of the studies was between 16 and 77 months. DIGU was found superior to TIPU in decreasing meatal/neourethral stenosis (p = 0.02, 95% CI 0.02-0.78). All other parameters were found comparable including overall complications, fistula and glans dehiscence rates. Success rates were similar among the groups ranging between 48% and 96% for DIGU and 43-96% in the TIPU group. The lack of standardization in the definition of complications and success was the major limitation of this study. - Conclusions - Using an inlay graft during primary hypospadias repair decreases the risk of meatal/neourethral stenosis. However, current evidence does not demonstrate superiority of DIGU over TIPU in terms of treatment success and overall complication rates.
Gesehen am 18.10.2021